Postharvest Handling Practices and Perception of Potato Safety among Potato Traders in Nairobi, Kenya - Consolata Nolega Musita; Michael Wandayi Okoth; George Ooko Abong’ (International Journal of Food Science)
Postharvest handling of the potato is an important factor not only in preventing postharvest losses but also in maintaining its safety and nutritional quality. Exposure of the potato to unfavorable conditions such as light, extreme temperatures, and bruising can result in accumulation of glycoalkaloids, which are toxic substances. This study was a cross-sectional survey which aimed to investigate the postharvest handling practices of potatoes and perception of potato safety among open air market traders in Nairobi County, Kenya. Information was collected from 100 potato traders using a semistructured questionnaire that assessed postharvest handling practices such as potato transportation, exposure to sunlight, and storage. Results indicated that most of the potatoes (88%) took one day to be transported to the market, with the storage period at the market ranging from 2 to 3 days for most traders (42%). Forty-seven percent (47%) of the vehicles and hand-pulled carts used to transport potatoes had open backs, while 53% had closed backs. Over half (69%) of the potatoes in the markets were directly exposed to sunlight, with 75% of the traders leaving their potatoes in the open covered with a polythene bag after the day’s activities. Greening, sprouting, or bruised potatoes were mostly sold as seed, sold to restaurants and French fries vendors, or sold to consumers at a lower price. More than half of the traders did not think that consumption of greened potatoes is harmful to health. The results clearly show that there is poor handling of the potatoes by the traders which increases the risk of consumer exposure to glycoalkaloids. There is, therefore, a need to create awareness among traders on appropriate postharvest handling of potatoes to protect consumer health and reduce economic losses as well.